2017
DOI: 10.1177/1060028017726795
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Apixaban Prescribing Patterns for Nonvalvular Atrial Fibrillation in Hospitalized Patients

Abstract: The majority of apixaban orders for NVAF were based on FDA-approved dosages after provider entry and pharmacist review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 8 publications
3
30
0
1
Order By: Relevance
“…Real‐world studies such as REVISIT‐US (real‐world evidence on stroke prevention in patients with atrial fibrillation in the USA) highlighted that reduced doses are more frequent in routine clinical practice when compared with clinical trials . In accordance with REVISIT‐US, 15.5% patients administered with apixaban received a reduced dose of 2.5 mg, whereas this was only 4.6% in the ARISTOTLE trial.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Real‐world studies such as REVISIT‐US (real‐world evidence on stroke prevention in patients with atrial fibrillation in the USA) highlighted that reduced doses are more frequent in routine clinical practice when compared with clinical trials . In accordance with REVISIT‐US, 15.5% patients administered with apixaban received a reduced dose of 2.5 mg, whereas this was only 4.6% in the ARISTOTLE trial.…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, a real‐world study conducted by Nguyen et al reported a reduced‐dose prescribing rate of 20.8%, which is also significantly higher than the percentage reported in ARISTOTLE. Regarding rivaroxaban, 17.3% of the patients from REVISIT‐US study and 21.7% from Nguyen et al study received a dose of 15 mg, similarly to 20.7% of the patients enrolled in ROCKET AF (reference clinical trial of rivaroxaban) . SPRINT AF also assessed the prevalence of Canadian patients eligible for the reduced dose of apixaban or rivaroxaban.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations